THE INFLUENCE OF LENGTH CUTS TRAILING EDGE ON FLOW CHARACTERISTICS IN THE RAILWAY HELM USING COMPUTATIONAL FLUID DYNAMICS - Syamsuri Syamsuri; Eky Novianarenti; Khoiri Huda (VANOS Journal of Mechanical Engineering Education, 2018)
There are many important reviews about the flow characteristics in the body of the racing bike helmet caused by the relative motion of the air along the Trailing Edge shape. The lines formed in such a way in the speed field will form a streamline stream so that the lines are in line with the flow at each point in the flow field. Thus, the streamline will form a pattern of airflow around the helmet. This aerodynamic characteristic study was performed on time meter helmet body visualized numerically using Computational Fluid Dynamics (CFD) with Solid Work Flow Simulation software. With variation of Trailing Edge 25 mm, 75 mm, 125 mm. Urgency research about helm time trial is believed to provide information about the flow that occurred. The result shows that the drag coefficient reduction that occurs on the cut variation of 75 mm compared with other variations on the Reynolds number 1.16 x 105 of 0.395.